Effect of the associated application between Rhizobium leguminosarum and efficient microorganisms on common bean production - Hurtado, Alexander Calero [UNESP]; Díaz, Yanery Pérez; Rodríguez, Elieni Quintero; Viciedo, Dilier Olivera [UNESP]; Calzada, Kolima Peña [UNESP] (My University, 2019)
To evaluate the relationship between different application forms of efficient microorganisms and the inoculation with Rhizobium in the morphological and productive behavior of common beans, an experiment at Cooperativa de Creditos y Servicios Martires de Taguasco, Sancti Spiritus, Cuba, was developed from October 2012 to January 2013 using the Cuba Cueto cultivar. Two factors were evaluated, the first was the use of Rhizobium (without and with 1 kg/46 kg of seed), and the second was four application forms of efficient microorganisms, without (0), to the furrow (100 mg/L), foliar (100 mg/L) and the associated (furrow plus foliar). The morphological and productive indicators established were: The average number of leaves per plant, plant height (cm), legumes per plant, grains per legumes, the mass of 100 grains (g/100 seeds), and yield (t/ha). The results showed that the best form of efficient microorganisms application was the associated form (furrow plus foliar) compared with the others, as it increased in 153.23 % the morphological and productive parameters evaluated, such as leaf production, plant height, legumes per plant, grains per legumes, mass of 100 seeds and grain yield when they were not inoculated with Rhizobium. Likewise, these same parameters increased 100 % when inoculated with Rhizobium and compared to the control treatment.
Keywords: Biofertilizers; Crop yield; Foliar application; Phaseolus vulgaris; Seed inoculation; Soil inoculation